Kajian Gerak Jatuh Bebas dengan Persamaan Lagrangian & Newtonian sebagai Bahan Ajar Fisika Kelas X - Siti Rachmawati; Azizah Zahro Ibrahim; Salsha Putri Fajriani; Indri Febilioni (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract This article contains a study on free fall motion. This study aims to calculate the free fall equations of motion using the Lagrangian and Newtonian equations and then compare them. The study was conducted through experimental activities in a virtual laboratory using a computer-assisted experimental tool called Algodoo with the simulation title